THEORETICAL PREDICTION OF SINGLE-SITE SURFACE-PROTONATION EQUILIBRIUM CONSTANTS FOR OXIDES AND SILICATES IN WATER - Sverjensky D.A.; Sahai N. (My University, 1996)
The equilibrium constants for surface protonation of solid oxides and silicates can be estimated from theoretical considerations and known properties of the solids for use in the constant capacitance, diffuse double layer or triple layer models of surface complexation. The theoretical considerations take into account Born solvation theory for the adsorbing proton, electrostatic interactions of the adsorbing proton with a surface oxygen and an underlying metal, and an intrinsic binding of the proton to the surface. As a consequence, the equilibrium constants for the νth (ν = 1 or 2) surface protonation reaction on the kth solid can be expressed in terms of the inverse of the dielectric constant of the solid (1εk) and an average Pauling bond strength per angstrom (srM-OH) for the solid according tolog Kν = Mν(1εk) - Bν(srM-OH) + log K''ii,ν, where the coefficients Mν, Bν, and K''ii,ν are constants characteristic of all oxides and silicates for each surface complexation model. Evaluation of these constants using experimental data for TiO2, γ-alumina, Al2O3, FeOOH, Fe(OH)3, silica, quartz, and kaolinite permits widespread prediction of surface protonation equilibrium constants from the known bulk structure properties 1εk andsrM-OH . Such predictions should replace attempts to estimate surface protonation equilibrium constants for solids from empirical correlations with aqueous equilibrium constants. Surface protonation constants should also not be estimated from correlations with only the Pauling bond strength because these neglect specific treatment of solvation. Each individual oxide or silicate is expected to have its own unique surface characteristics, depending on the bonding in the bulk crystal structure connected to the surface. It follows that the bonding in surface protonated species is probably far more analogous to that in the bulk crystal structure than to the bonding in protonated aqueous species.